Assessment of the relationship between magnetotransport and magnetocaloric properties in nano-sized La0.7Ca0.3Mn1-xNixO3 manganite (2018)
The effect of Ni2+substitution on the magneto-transport properties and the concomitant relationship with the magnetocaloric function of nano-sizedLa0.7Ca0.3Mn1−xNixO3(x = 0, 0.02, 0.07, and 0.10) perovskite manganites are reported. All the samples were synthesized using the auto-combustion method. X-raydiffraction analysis studies confirmed the phase purity of the synthesized samples. The substitution of Mn3+ions with Ni2+ions in the La0.7Ca0.3MnO3lattice wasalso verified using this technique. Rietveld analysis indicated that the volume of the unit cell increased with increasing Ni2+content. Zero-field-cooled andfield-cooled magnetization showed that all samples underwent a paramagnetic-ferromagnetic phase transition, which was concomitant with a metal-insulator transition.